Effect of welding fumes on the cardiovascular system: a six-year longitudinal study - Taj, Tahir; Gliga, Anda R; Hedmer, Maria; Wahlberg, Karin; Assarsson, Eva; Lundh, Thomas; Tinnerberg, Håkan; Albin, Maria; Broberg, Karin (Scandinavian journal of work, environment & health, 2021)
Objective This study investigated whether low-to-moderate exposure to welding fumes is associated with adverse effects on the cardiovascular system. Methods To test this, we performed a longitudinal analysis of 78 mild steel welders and 96 controls; these subjects were examined twice, six years apart (ie, timepoints 1 and 2). All subjects (male and non-smoking at recruitment) completed questionnaires describing their health, work history, and lifestyle. We measured their blood pressure, endothelial function (by EndoPAT), and risk markers for cardiovascular disease [low-density lioprotein (LDL), homocysteine, C-reactive protein]. Exposure to welding fumes was assessed from the responses to questionnaires and measurements of respirable dust in their breathing zones adjusted for use of respiratory protection equipment. Linear mixed-effect regression models were used for the longitudinal analysis. Results Median respirable dust concentrations, adjusted for respirable protection, of the welders were 0.7 (5-95 percentile range 0.2-4.2) and 0.5 (0.1-1.9) mg/m at timepoints 1 and 2, respectively. Over the six-year period, welders showed a statistically significant increase in systolic [5.11 mm Hg, 95% confidence interval (CI) 1.92-8.31] and diastolic (3.12 mm Hg, 95% CI 0.74-5.5) blood pressure compared with controls (multi-variable adjusted mixed effect models). Diastolic blood pressure increased non-significantly by 0.22 mm Hg (95% CI -0.02-0.45) with every additional year of welding work. No consistent significant associations were found between exposure and endothelial function, LDL, homocysteine, or C-reactive protein. Conclusion Exposure to welding fumes at low-to-moderate levels is associated with increased blood pressure, suggesting that reducing the occupational exposure limit (2.5 mg/m for inorganic respirable dust in Sweden) is needed to protect cardiovascular health of workers.